Statins—Their Effect on Lipoprotein(a) Levels - Marcin Mateusz Granat (Reviews in Cardiovascular Medicine)
Lipoprotein(a) (Lp(a)) serum concentration plays a crucial role as a risk factor in cardiovascular diseases and is gaining more and more attention. Patients with elevated lipoprotein(a) levels are often prescribed statins as they also have high concentrations of low-density lipoprotein cholesterol (LDL-C). Statins are drugs that successfully decrease LDL-C, but their effectiveness in Lp(a) levels reduction is uncertain. The aim of this study was to evaluate if statin therapy can affect Lp(a) concentration. A literature search on databases like PubMed, Oxford Academic, ScienceDirect, Embase, The Cochrane Library, Scopus, and Springer Link was conducted from 1 May to 10 August 2024 with the aim of finding studies concerning the effect of statins on Lp(a) levels. Only randomised control studies and studies with a placebo/comparator arm were included. For calculations, SPSS Statistics software version 29 was used. The risk of bias for this study was assessed using the revised Cochrane risk-of-bias tool for randomised trials. Overall, 43 studies (13,264 participants in study arms and 11,676 in control arms) were included in the analysis. The mean difference of absolute change in Lp(a) concentration for all 43 studies equaled 0.22 mg/dL and was not clinically significant. Egger's regression-based test resulted in no risk of bias in this study (p = 0.404). In conclusion, statin therapy does not significantly affect Lp(a) levels. Results of this work suggest that people with high Lp(a) levels will not change their Lp(a)-associated cardiovascular (CV) risk by statin administration.